Using ICT to Enhance the Management of the Natural & Cultural Heritage Resources of Old Oyo National Park for E-Tourism Development - Olatubosun, Olabode; Oladipo, Oladeji Sunday; Babatunde, Iwasokun Gabriel (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper describes the conceptualization of Old Oyo National Park seeking an intervention for improve collaboration and communication internally across functional and departmental boundaries through the use of ICT. Eighteen natural and cultural heritage resources of ecotourism values were indentified in the Park, in addition to the nine art and craft practiced in these communities and eight annual cultural events. A detail assessment of the level of development of the cultural and natural features in the Old Oyo National Park was carried out based on the three component of tourist destination, viz; attraction, amenities and accessibility. The gridded map of the locations of these ecotourism features was also presented. An e-tourism designed for the park has the basic component of catalog of product, shopping cart, and check out, payment gateway (payment processing network), customer account, internet merchant account and business account. Customers can browse the catalog of tourism product and shops cart it. The gateway component accepts credit card details and sends to the payment gateway for authorization on the premise of adequate security using the SSL primitives. Funds are reserved into the customer account and later transfer to merchant account, and then to the business account of the park.